Fundamentals of Entrepreneurship ENT300 i-Campus Tuition Centre / Glenn Eric Ringib... [et al.] - Ringib, Glenn Eric; Kalong, Robica; Giman, Franklin; Wan Zain, Sharifah Najian; Brau, Miceelle Bau (2012)
The name of our Company is i-Campus Tuition Centre. Our major business is educational business by providing services or advance knowledge to student. This business has been decided on the form of partnership. Each partner contributes cartain amount of capital as agreed in agreement. We agreed that Glenn Eric Ringib as the General Manager, Sharifah Najian Binti Wan Zain as Marketing Manager, Franklin Anak Giman as Operational Manager, Robica Anak Kalong as the Administration Manager and Miceelle Bau Brau as the Financial Manager. The selection of the General Manager is based on the consensus among all the partners and selected based on experience, skills and ability.